Natural Killer Cells in Inflammatory Heart Disease - Ong, SuFey (Clin Immunol, 2016)
Despite of a multitude of excellent studies, the regulatory role of natural killer (NK) cells in the pathogenesis of inflammatory cardiac disease is greatly underappreciated. Clinical abnormalities in the numbers and functions of NK cells are observed in myocarditis and inflammatory dilated cardiomyopathy (DCMi) as well as in cardiac transplant rejection [1–6]. Because treatment of these disorders remains largely symptomatic in nature, patients have little options for targeted therapies [7, 8]. However, blockade of NK cells and their receptors can protect against inflammation and damage in animal models of cardiac injury and inflammation. In these models, NK cells suppress the maturation and trafficking of inflammatory cells, alter the local cytokine and chemokine environments, and induce apoptosis in nearby resident and hematopoietic cells [1, 9, 10]. This review will dissect each protective mechanism employed by NK cells and explore how their properties might be exploited for their therapeutic potential.